Training pharmacists in the stage-of-change model of smoking cessation and motivational interviewing: A randomized controlled trial. Issue 2 (October 2017) - Caponnetto, Pasquale; DiPiazza, Jennifer; Aiello, Maria Rosaria; Polosa, Riccardo
This study evaluated the effect of training pharmacists in the stage-of-change model for smoking cessation and motivational interviewing on smoking cessation outcomes. A training based on the stage-of-change model for smoking cessation and motivational interviewing was introduced to pharmacists. Pharmacists were randomly assigned to the intervention or control group. The control group attended a 3-hour training session, whereas the intervention group also attended a further 6-hour training session. At week 24, 12.2 percent of the smokers quit smoking in the intervention group, whereas 1.6 percent of the smokers quit smoking in the control group. The findings of this study showed that training pharmacists, in the stage-of-change model for smoking cessation and motivational interviewing, improves smoking reduction and cessation rates.